2020
DOI: 10.1093/femsec/fiaa103
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between iron limitation, light and carbon in the proteorhodopsin-containing Photobacterium angustum S14

Abstract: Iron (Fe) limitation is known to affect heterotrophic bacteria within the respiratory electron transport chain, therefore strongly impacting the overall intracellular energy production. We investigated whether the gene expression pattern of the light-sensitive proton pump, proteorhodopsin (PR), is influenced by varying light, carbon and Fe concentrations in the marine bacterium Photobacterium angustum S14 and whether PR can alleviate the physiological processes associated with Fe starvation. Our results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 65 publications
(79 reference statements)
0
9
1
Order By: Relevance
“…By stationary phase, iron-containing alcohol dehydrogenase YqhD, bacterioferritin Bfr, ferric iron ABC transporter, S -(hydroxymethyl)glutathione dehydrogenase FrmA, and a glutaredoxin were all more highly expressed under C limitation as well. While previous studies have observed PR expression regulation related to iron limitation ( 19 , 40 ), the iron-replete conditions in this study highlight that photoheterotrophs regulate Fe-containing proteins in response to C and N limitation as well.…”
Section: Resultscontrasting
confidence: 65%
See 4 more Smart Citations
“…By stationary phase, iron-containing alcohol dehydrogenase YqhD, bacterioferritin Bfr, ferric iron ABC transporter, S -(hydroxymethyl)glutathione dehydrogenase FrmA, and a glutaredoxin were all more highly expressed under C limitation as well. While previous studies have observed PR expression regulation related to iron limitation ( 19 , 40 ), the iron-replete conditions in this study highlight that photoheterotrophs regulate Fe-containing proteins in response to C and N limitation as well.…”
Section: Resultscontrasting
confidence: 65%
“…The slightly enhanced transcription of PR in the dark under C limitation was reflected in modestly elevated protein abundance during stationary phase, but no light-dark difference in protein abundance was observed during N-limited growth. In contrast, in Photobacterium angustum S14, PR protein expression is clearly regulated by blue light ( 19 ). Prior work has shown that Vibrio campbellii BAA-1116 induces PR transcription with both light and nutrient starvation and Vibrio sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations